Influence of organic manure on physical properties of vertisol under cotton cultivation - KHUSPURE, JAYSHREE A.; BHOYAR, S. M.; DESHMUKH, P. W. (Journal of Soil and Water Conservation, 2020)
The experiment was laid out in RBD with eight treatments and three replications. This two year organic cotton field investigation aimed at studying the effect of different levels of manures on physical properties of the Vertisol at Cotton Research Unit, Central research station, Dr. Panjabrao Deshmukh Krishi Vidhyapeeth, Akola under rainfed condition during Kharif season of 2013-14 and 2014-15. The organic inputs used were FYM, vermicompost, in-situ green manure sunhemp and castor cake. Application of 10 t FYM ha-1 improved bulk density, porosity, hydraulic conductivity, available water capacity, mean weight diameter of soil under rainfed condition. Significantly highest seed cotton yield was recorded in the treatment of FYM @ 10 t ha-1 (15.39 q ha-1), followed by the treatment castor cake @ 500 kg-1 (15.04 q ha-1). Similarly, significantly highest dry matter yield was also recorded with FYM @ 10 t ha-1 (85.36 q ha-1) which was at par with castor cake @ 500 kg-1 (36.53 q ha-1).